2001
DOI: 10.1136/heart.85.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and aerobic capacity in adult patients following modified Fontan procedure

Abstract: Objective-To examine cardiopulmonary performance in 52 adult patients with a Fontan circulation. Design-Retrospective cohort study. Values of maximum oxygen uptake (VO 2 max), maximum heart rate (HRmax), forced vital capacity (FVC), and forced expiratory volume in one second (FEV 1 ) were compared with predictive values for diVerent age groups. Patients were further subdivided into those with a pulmonary artery connection (RA-PA) or right atrium to right ventricle conduit (RA-RV). Results-At late follow up (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 24 publications
5
48
2
Order By: Relevance
“…169,170 The estimated prevalence of RLD in adults with CHD has been reported to be as high as 44% to 56%, with an even higher prevalence in the setting of certain lesions, particularly patients with a history of Fontan palliation (prevalence of 89%) and TOF (prevalence of 76%). 170,171 These studies suggest that the prevalence of spirometry-diagnosed RLD in the ACHD population is markedly higher than in the general adult population, where it is reported to be ≈9.2%.…”
Section: Pulmonary Diseasementioning
confidence: 96%
“…169,170 The estimated prevalence of RLD in adults with CHD has been reported to be as high as 44% to 56%, with an even higher prevalence in the setting of certain lesions, particularly patients with a history of Fontan palliation (prevalence of 89%) and TOF (prevalence of 76%). 170,171 These studies suggest that the prevalence of spirometry-diagnosed RLD in the ACHD population is markedly higher than in the general adult population, where it is reported to be ≈9.2%.…”
Section: Pulmonary Diseasementioning
confidence: 96%
“…Not surprisingly, therefore, factors that impair chronotropic response to exercise such as ␤-blockade or abnormal cardiac rhythm were associated with a lower peak V O 2 . Previous studies have shown that some ACHD patients have impaired pulmonary function 15 and depressed peak heart rate. 5 The present study extends these findings by demonstrating that both heart rate response and pulmonary function correlate positively with peak V O 2 even after accounting for other physiological parameters.…”
Section: Other Correlates Of Exercise Intolerance In Achdmentioning
confidence: 98%
“…Serial evaluations facilitate detection of functional decline, although patients may report that they are "normal." One study 52 showed that peak oxygen uptake (V o 2 max) in a group of 41 patients with CCTGA ranged from 11 to 22 mL per kg per min, which is the equivalent of only 30% to 50% of normal control values.…”
Section: Exercise Testingmentioning
confidence: 99%